Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/jacs.1c04108
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Redox Non-innocent Hydrogen-Bonding in Cu(I)-Diazene Complexes

Abstract: The life-sustaining reduction of N2 to NH3 is thermoneutral yet kinetically challenged by high-energy intermediates such as N2H2. Exploring intramolecular H-bonding as a potential strategy to stabilize diazene intermediates, we employ a series of [ xHetTpCu]2(μ-N2H2) complexes that exhibit H-bonding between pendant aromatic N-heterocycles (xHet) such as pyridine and a bridging trans-N2H2 ligand at copper­(I) centers. X-ray crystallography and IR spectroscopy clearly reveal H-bonding in [pyMeTpCu]2(μ-N2H2) whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 90 publications
(141 reference statements)
1
14
0
Order By: Relevance
“…With interest in dinitrogen (N 2 ) reduction and intermediates relevant thereto, in 2021 Shafaat and Warren studied the N 2 coordination chemistry of a pyridine-substituted trispyrazolylborate (Tp) copper(I) compound (Scheme 26). 66 As a product of two-electron, two-proton reduction, diazene (HNQNH) is a reactive small-molecule, that at room temperature, undergoes disproportionation to N 2 and hydrazine (N 2 H 4 ). In this study, the authors showed that {[ xHet TpCu] 2 (m-N 2 H 2 )} exhibited pendant hydrogen bonding interactions with a pyridine positioned in the SCS.…”
mentioning
confidence: 99%
“…With interest in dinitrogen (N 2 ) reduction and intermediates relevant thereto, in 2021 Shafaat and Warren studied the N 2 coordination chemistry of a pyridine-substituted trispyrazolylborate (Tp) copper(I) compound (Scheme 26). 66 As a product of two-electron, two-proton reduction, diazene (HNQNH) is a reactive small-molecule, that at room temperature, undergoes disproportionation to N 2 and hydrazine (N 2 H 4 ). In this study, the authors showed that {[ xHet TpCu] 2 (m-N 2 H 2 )} exhibited pendant hydrogen bonding interactions with a pyridine positioned in the SCS.…”
mentioning
confidence: 99%
“…As highlighted in the introduction, stable dicopper diazene complexes with appended H atom acceptors have been used to study the energetics of H atom transfer at N 2 H 2 without an initial exogenous electron transfer [15a] . In order to compare to the Sellmann system, we chose to calculate the energy of the N 2 species that would be formed by PCET from N 2 H 2 in stable diazene complex 1‐L 1 .…”
Section: Resultsmentioning
confidence: 99%
“… Limiting resonance structures of the dicopper‐N 2 H 2 complexes (a) and (b), and the N 2 tautomer (c) [15a] . The hydrogen bond is considered to be transferrable in the resonance structures, similar to the “resonance‐assisted hydrogen bonding” concept [21] …”
Section: Introductionmentioning
confidence: 99%
“…5b, the intensities of the ν 1 and ν 3 modes are obviously stronger in the K + -containing electrolyte solution than that in the Na + -containing electrolyte solution, verifying the vital role of K + in the insertion of NO 3 − . As the reaction proceeds, a vibration mode located at 548 cm −1 appears, which can be assigned to the Cu-N bond [53]. The intensity increases gradually with the reaction time, suggesting that NO 3 − or the intermediate species are bonded to the catalyst surface by forming a Cu-N bond.…”
Section: Impact Of K + and In Situ Raman Spectroscopy Characterizationmentioning
confidence: 99%